Preschool Curricula and Professional Development Features for Getting to High-Quality Implementation at Scale: A Comparative Review Across Five Trials - Christina Weiland; Meghan McCormick; Shira Mattera; Michelle Maier; Pamela Morris (SAGE Publishing, 2018)
Experts have heralded domain-specific play-based curricula coupled with regular coaching and training as our "strongest hope" for improving instructional quality in large-scale public preschool programs. Yet, details from different evaluations of the strongest hope model are not systematically compiled, making it difficult to identify specific features across studies that distinguish the most successful implementation efforts. We performed a cross-study review across five diverse large-scale evaluations (n = 6,500 children and n = 750 teachers across 19 localities and multiple auspice types) to identify common features that have characterized successful implementations of this model to date. We identified six features in our exploratory review that may help to flesh out the strongest hope model for localities considering it-a significant focus on specific instructional content, inclusion of highly detailed scripts, incorporation of teacher voice, time for planning, use of real-time data, and early childhood training for administrators. These six features provide more specific guidance for practitioners and help meet calls in preschool and K-12 for more synthesis of implementation lessons from large-scale research trials.